Borrowing from a Bigtech Platform - Li, Jian; Pegoraro, Stefano (Review of Financial Studies, 2026)
Abstract We model credit competition between a bigtech platform and a bank lending to a merchant under limited commitment and asymmetric information about the merchant’s incentives to default. The platform leverages its control over a marketplace to enforce partial loan repayments, enabling it to serve certain unbanked borrowers. When directly competing with the bank, the platform gains an endogenous screening advantage as borrowers with stronger incentives to default self-select into bank loans to avoid the platform’s enforcement. Whereas the platform improves financial inclusion for unbanked borrowers, social welfare may decline because the bank tightens credit in response to adverse screening.